IMPLEMENTASI WHATSAPP API UNTUK PERINGATAN DINI KEPADA ORANG TUA PESERTA DIDIK DI SEKOLAH - Moh. Ali Fikri; Ahmad Lubis Ghozali; Dian Pramadhana (Politeknik Negeri Indramayu, 2023)
The rapid development of information systems in the current era of globalization has made almost all aspects of life unavoidable from the use of computer devices, especially in educational institutions. The number of SMA/equivalent in Indonesia is 15,497, namely in public schools there are 7,203 (46.48%) and private schools 8,294 (53.52%). West Java Province has the highest number of schools, namely 1,823 schools. Meanwhile, Indramayu Regency has 89 SMA/equivalent with details of 26 state and 63 private. One of them is SMA NU Tenajar Kidul. The school has problems with the presence of students. Often students do not enter school without explanation. However, after follow-up was carried out by the school, they received information from the parents of the students that their children were leaving home from home. So that these students are truant and cause not get knowledge in school. The need for a touch of technology that can bridge the school with parents of students. So that when there is a problem that one of the students is absent, the school can provide information to parents quickly and accurately. Therefore WhatsApp API is the right choice to provide attendance information to parents. The system was built using the nodeJS programming language and got the test results of 40 messages, getting the message sending process time of 0 milliseconds. While the time needed by the API to process the message sending is the longest 0.10522 milliseconds. If you calculate the average length of the message sending process, it is equal to 0.037826 milliseconds. Thus the WhatsApp API that has been built is very effective with performance under 1 second. All messages stored in the table are 100% sent.